Volatility spillover effects between financial markets: Evidence from the US and China - Xie, Meng-Xue (2017)
The interdependence between the developed financial markets and those markets in emerging countries has increasingly strengthened by capital liberalisation and globalisation. Especially, during the significant financial crises, how the negative volatility spillover effects may influence the performance of emerging markets and is there any difference between the crisis and non-crisis periods. In this paper, we examine the volatility-level spillover effects between the US and China’s stock markets and foreign exchange markets during April 2006 to March 2017 based on a vector autoregressive model, including both trend and bursts in the evolution of the stock and foreign exchange markets. The empirical results show that there is a negative volatility spillover effect between the US and China financial markets, presented in an asymmetric manner but varying across different time horizon, making it difficult to distinguish a clear and consistent pattern of the shock spillover effects between those two nations during the whole sample period. However, we find that those markets who send more spillovers to others tend to receive more shocks from other markets as well. All in all, the transmission effect between the US and China are increasing sharply in a bilateral manner, which is even more significant than the fluctuation arising from 2007 financial crisis.